The panorama of the feeding of children with attention deficit hyperactivity disorder (Research, Society and Development, 2022)
This article aims to identify the disorder, as well as its long-term consequences and forms of drug treatments along with adequate nutritional support. The Attention Deficit Disorder with Hyperactivity is a neurobiologic disorder which affects mostly children and adolescents. This disorder has been studied and analyzed more often and portrayed as a serious public health problem. It is related to genetic factors which manifest from childhood and extend to adulthood. The present study aimed to update nutritional interventions and treatments applied to children with the disorder. The methodology applied for the study development consisted of a narrative literature review on attention deficit disorder with hyperactivity. Psychosocial and genetic conditions, associated with an inadequate food intake may play a major role in disease development. A proper diet, rich in essential nutrients that are required for the child’s development, may improve symptoms of this disorder. The nutritionist is the only professional trained to plan an adequate diet that contemplates energy and necessary nutrients to improve signs and symptoms of attention deficit disorder with hyperactivity.